2014
DOI: 10.1530/rep-14-0304
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma-derived growth factor: from the bovine uterus to the in vitro embryo culture

Abstract: Early in cow embryo development, hepatoma-derived growth factor (HDGF) is detectable in uterine fluid. The origin of HDGF in maternal tissues is unknown, as is the effect of the induction on developing embryos. Herein, we analyze HDGF expression in day 8 endometrium exposed to embryos, as well as the effects of recombinant HDGF (rHDGF) on embryo growth. Exposure to embryos did not alter endometrial levels of HDGF mRNA or protein. HDGF protein localized to cell nuclei in the luminal epithelium and superficial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…Indeed, several proteins whose genes were expressed by the oviduct and endometrium in this study have been shown to modify embryonic development in the cow. These include activin A (Trigal et al, 2011;Kannampuzha-Francis et al, 2016), bone morphogenetic protein 4 (BMP4; La Rosa et al, 2011), CSF2 (Loureiro et al, 2009;Denicol et al, 2014), connective tissue growth factor (CTGF; Kannampuzha-Francis et al, 2016), DKK1 (Denicol et al, 2014), epidermal growth factor (EGF; Sakagami et al, 2012), fibroblast growth factor 2 (FGF2; Fields et al, 2011), hepatomaderived growth factor (HDGF; Gómez et al, 2014), IGF1 (Jousan and Hansen, 2007;Bonilla et al, 2011), Table 1. Genes whose expression in the oviduct ipsilateral to the side of ovulation was affected by day of the estrous cycle within the first 7 d after ovulation 1 interleukin 1 β (IL1β) (Paula-Lopes et al, 1998), LIF (Mohamed et al, 2004;Neira et al, 2010;Mo et al, 2014), transforming growth factor beta (TGFβ; Neira et al, 2010), and WNT7A (Tribulo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several proteins whose genes were expressed by the oviduct and endometrium in this study have been shown to modify embryonic development in the cow. These include activin A (Trigal et al, 2011;Kannampuzha-Francis et al, 2016), bone morphogenetic protein 4 (BMP4; La Rosa et al, 2011), CSF2 (Loureiro et al, 2009;Denicol et al, 2014), connective tissue growth factor (CTGF; Kannampuzha-Francis et al, 2016), DKK1 (Denicol et al, 2014), epidermal growth factor (EGF; Sakagami et al, 2012), fibroblast growth factor 2 (FGF2; Fields et al, 2011), hepatomaderived growth factor (HDGF; Gómez et al, 2014), IGF1 (Jousan and Hansen, 2007;Bonilla et al, 2011), Table 1. Genes whose expression in the oviduct ipsilateral to the side of ovulation was affected by day of the estrous cycle within the first 7 d after ovulation 1 interleukin 1 β (IL1β) (Paula-Lopes et al, 1998), LIF (Mohamed et al, 2004;Neira et al, 2010;Mo et al, 2014), transforming growth factor beta (TGFβ; Neira et al, 2010), and WNT7A (Tribulo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the unclarified system(s) of secretion, the exogenous administration of HDGF stimulates the proliferation of various cell types, including benign and malignant cells [ 26 , 27 , 28 , 29 , 30 , 31 ]. In addition, the exogenous administration of HDGF enhances the phosphorylation of mitogen-activated protein kinase (MAPK) in gastric epithelial cells and endothelial cells [ 32 , 33 ].…”
Section: Hdgf As a Novel Unique Growth Factormentioning
confidence: 99%
“…Although HDGF was isolated from a hepatoma cell line, previous studies have shown that it plays important roles in the development and tissue repair of numerous normal organs, including the liver, kidneys, lungs and gut [ 27 , 28 , 29 , 30 , 31 ]. In addition, Everett et al [ 39 ] reported the functional involvement of HDGF in the development of and tissue repair in the cardiovascular system.…”
Section: Hdgf As An Angiogenic Factormentioning
confidence: 99%
“…Intrinsic apoptosis pathway proceeds at least by well-defined environmental perturbations (Galluzzi et al, 2018). The bovine embryo has been identified as responsive to some of such alterations: (1) Endoplasmic reticulum (ER) stress, which simultaneously increases expression of ER stress (Glucose-Regulated Protein, 78 kDa (GRP78), Activating Transcription Factor 4 (ATF4), Activating Transcription Factor 6 (ATF6), Regulator Of G Protein Signaling 1 (RGS1) and X-Box Binding Protein 1 (XBP1)] and pro-apoptotic [C/EBP Homologous Protein (CHOP) and BCL2 Associated X, Apoptosis Regulator (BAX)] genes, at the same time that development rates, cryotolerance, cell survival and apoptotic cell rates improve (Yoon et al, 2014;Khatun et al, 2020); (2) ROS overload can also trigger apoptosis and developmental affectance (Huang and Chan, 2017;Luo et al, 2020); (3) Irregular DNA structures, out of which only a subset can be identified by TUNEL (Gjorret et al, 2003;Leidenfrost et al, 2011); abnormal segregation of chromosomes in mitosis is a possible origin of such structures (Gjorret et al, 2003); (4) Mitotic effects, where apoptosis was observed in response to multinucleate cells (Paula and Hansen, 2008) and cytokinesis becomes blocked leading to a "mitotic catastrophe" by checkpoint activation (Huang et al, 2005); (5) Specific miRNAs that trigger apoptosis, since slow-cleaving bovine embryos in culture release miRNA-30c, which targets cyclin-dependent kinase 12 (CDK12) and lead to apoptosis (Juan et al, 2016;Lin et al, 2019), although it is unknown whether dead cells or live cells with a commitment release miR-30c; 6) Growth factors removal as shown by specific growth factors identified in the genital tract that reduce apoptosis when added to IVC (Trigal et al, 2011;Gomez et al, 2014). In pigs, vascular endothelial growth factor (VEGF) decreased in parallel to an increase in embryo development, concomitant with a reduction in mRNA abundance of caspase 3 (CASP3) and increased BCL2 Apoptosis Regulator (BCL2) and Nuclear Factor, Erythroid 2 Like 2 NRF-2 (Biswas et al, 2018).…”
Section: Intrinsic Apoptosismentioning
confidence: 99%